2019
DOI: 10.1038/s41419-019-1610-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: FABP4 contributes to renal interstitial fibrosis via mediating inflammation and lipid metabolism

Abstract: Fatty acid binding protein 4 (FABP4), a subtype of fatty acid-binding protein family, shows critical roles in metabolism and inflammation. However, its roles on regulating renal interstitial fibrosis (RIF) remain unclear. In this work, LPS-stimulated in vitro models on NRK-52E and NRK-49F cells, and in vivo UUO models in rats and mice were established. The results showed that comparing with control groups or sham groups, the expression levels of α-SMA, COL1A, COL3A, IL-1β, IL-6, and TNF-α in LPS-stimulated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…Additionally, S4 was a prominent subset that was enormously increased in the P8 (10.2%) compared to the P3 (0.3%) hearts (Table 1 ). In particular, there were a lot more P8 than P3 cells expressing genes that encoded for extracellular matrix proteins or secreted proteins associated with fibroblast activation and fibrosis such as S100a8 16 , Fabp4 17 , Sparc 18 , Mfap4 19 and Mfap5 20 ; or collagen proteins such as Col3a1 , Col1a1 , Col1a2 , Col4a1 and Col4a2 (Figure 4 E). In the cardiovascular system, FABP4 has been demonstrated to cause pressure overload-induced cardiac hypertrophy 21 ; and can be therapeutically targeted against severe atherosclerosis 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, S4 was a prominent subset that was enormously increased in the P8 (10.2%) compared to the P3 (0.3%) hearts (Table 1 ). In particular, there were a lot more P8 than P3 cells expressing genes that encoded for extracellular matrix proteins or secreted proteins associated with fibroblast activation and fibrosis such as S100a8 16 , Fabp4 17 , Sparc 18 , Mfap4 19 and Mfap5 20 ; or collagen proteins such as Col3a1 , Col1a1 , Col1a2 , Col4a1 and Col4a2 (Figure 4 E). In the cardiovascular system, FABP4 has been demonstrated to cause pressure overload-induced cardiac hypertrophy 21 ; and can be therapeutically targeted against severe atherosclerosis 22 .…”
Section: Resultsmentioning
confidence: 99%
“…6a ), suggesting GADD45α interacts with PPARγ. To examine whether the interaction regulates the transcriptional activities of PPARγ, we performed a chromatin immunoprecipitation and luciferase reporter assay of FABP4, which is a downstream target of PPARγ and directly regulated by PPARγ 37 39 . The chromatin immunoprecipitation (ChIP) and luciferase reporter assays indicated that PPARγ directly bound to the promoter of FABP4 to enhance FABP4 gene transcription (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that GADD45α interacts with PPARγ and upregulates its transcriptional activity. The activated form of PPARγ is well-accepted to be upstream of FABP4, which is also known as adipocyte protein 2 (aP2) and is involved in the intracellular fatty acid transport and glucose and lipid homeostasis in mature adipocytes 37 39 . The promoter of FABP4 has been widely used in adipocyte-specific recombination in mice 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies demonstrated that FABP4-deficient macrophages suppressed inflammatory signaling, attenuated the activation of NF-κB pathway, and decreased endoplasmic reticulum stress (21). A recent study has reported that FABP4 deteriorated RIF via promoting NF-κB-mediated inflammation (14). It has been well recognized that inflammation is a key process leading to progressive renal fibrosis where intragraft macrophages, particularly activated macrophages, played crucial roles.…”
Section: Discussionmentioning
confidence: 99%